Eco-costs of sustainable construction waste management in Malaysia - Yahya, Khairulzan (Penerbit UTM, 2008)
Sustainable development is a development that taken the issue of environment as a priority besides on making whatever planning into reality. One of the key themes of 'sustainable development' is managing a waste (Williams, 1998). Sustainable waste management encourages the generation of less waste, the re-use, recycling and recovery of waste that is produced. Farmoso et al. (1999) defines waste as any losses produced by activities that generate direct or indirect costs but do not add any value to the product from the point of view of the client. While Symond (1999) define wastes as any substance or object, which the holder discards or intends, or is required, to discard. Construction activity requires and consumes a large amount of natural resources. Beside of negative impact to the environment due to depletion of natural resources, it may increases the amount of waste and pollution if no measurement to tackle the problem is taken. In Malaysia, the construction waste has cause a significant impact on the environmental and also increasing the concern of the society (Beguma, Siwar et al. 2006). Hence, this paper, review construction waste minimisation strategies, addresses the issues that are attributed to construction waste management and presents an integrated approach to whole life cycle management of construction waste. Finally, an attempt is made to model the ecocosts associated with construction waste.